Seorang Profesional Hubungan Masyarakat dalam Film Merek Kami Adalah Krisis - Rangga Wibowo; M.E Fuandy (Bandung Conference Series: Public Relations, 2021)
Abstract. Film is a mass media that has a function as entertainment, besides that the film also contains an informative, educative, and persuasive function. Film is also known as a medium of communication, film is an effective means to shape the perspective of society at large. A movie titled “Our Brand Is Crisis” is a movie about a public relations practitioner who tries to restore the image of a politician. This movie also tells a story about the troublesome life of a politician who has bad image in the eyes of public and media. The purpose of this research is to understand the Reality Level, Representation Level and Ideology Level of public relations role in the movie “Our Brand Is Crisis”. The research method is using the qualitative methods with semiotics approach, which is a science about signs. The theory used is John Fiske’s theory of Television Codes which focuses on the Reality Level, Representation level and Ideology Level. In this research the data collection techniques used are observation, documentation, literature study, and interviews. Conclusions: Portrait of the profession of public relations at the level of reality that is the code culture, appearance, dress, environment, behavior code, speech code, gesture code, expression code, discussion in the expression a major role Jane bodine, along with Pedro Castillo as a candidate senator or bolivian president. A portrait of the profession of public relations at the level representation addressed to the camera, code lighting, code, conflict code, music and the code dialogue. The more prominent at this level, the first to the camera and lighting that memvisualkan profession public relations as played by jane. A portrait of the profession of public relations at the level of an ideology which is the representation of sod used by the director of individualism profession for a professional Public Relations that handle a political campaign winning general bolivian president named pedro castillo packed visually on film in starring by sandra bullock as jane bodine. Abstrak. Film merupakan media massa yang memiliki fungsi sebagai hiburan, disamping itu juga film mengandung fungsi informatif, edukatif, dan persuasif. Film juga dikenal sebagai media komunikasi, film merupakan salah satu sarana yang efektif untuk membentuk perspektif masyarakat secara luas. Film “Our Brand Is Crisis” merupakan sebuah film yang mengangkat kisah tentang perbaikan citra dari seorang politikus oleh seorang praktisi public relations. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana level realitas, level representasi, dan level ideologi peran public relations dalam film “Our Brand Is Crisis”. Metode penelitian yang digunakan oleh peneliti adalah metode kualitatif dengan pendekatan semiotika John Fiske berfokus pada level Realitas, level Representasi, dan level Ideologi. Pada penelitian ini teknik pengumpulan data yang digunakan berupa observasi, dokumentasi, studi pustaka, dan wawancara. Simpulan Potret profesi public relations pada level realitas yaitu kode budaya seperti penampilan (appearance), kostum (dress), lingkungan (environment), kode kelakuan (behavior), kode dialog (speech), kode gesture (gerakan), dan kode expression (ekspresi) pembahasan dalam ekspresi peran utama Jane Bodine, berserta Pedro Castillo sebagai calon senator atau presiden Bolivia. Potret profesi public relations pada level representasi ditujukan kepada kode kamera, lighting, kode konflik, kode musik, dan kode dialog. Yang lebih menonjol dalam level ini, pertama pada kode kamera dan lighting yang memvisualkan profesi public relations yang diperankan oleh Jane. Potret profesi public relations pada level ideologi yaitu representasi ideologi yang digunakan oleh sutradara yaitu individualisme (individualism) profesi seorang professional public relations yang menangani kampanye politik pemenangan presiden Bolivia bernama Pedro Castillo yang dikemas secara visual pada film yang di bintangi oleh Sandra Bullock sebagai Jane Bodine.